2019
DOI: 10.3389/fams.2019.00039
|View full text |Cite
|
Sign up to set email alerts
|

Online Scent Classification by Ion-Mobility Spectrometry Sequences

Abstract: For ion-mobility spectrometry (IMS)-based electronic noses (eNose) samples of scents are markedly time-dependent, with a transient phase and a highly volatile stable phase in certain conditions. At the same time, the samples depend on various environmental factors, such as temperature and humidity. This makes fast classification of scents challenging. The present aim was to develop and test an algorithm for online scent classification that mitigates these dependencies by using both baseline measurements and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This approach only fails if the majority of channels fails or when the algorithm detects change points on multiple channels that are far from the real change points. Analysis of the data set collected for this paper and the data set used in [14] showed that both situations are improbable. Therefore, in this paper the Matrix form CUSUM algorithm using averages of detected change points is used.…”
Section: Matrix Form Cusummentioning
confidence: 96%
See 2 more Smart Citations
“…This approach only fails if the majority of channels fails or when the algorithm detects change points on multiple channels that are far from the real change points. Analysis of the data set collected for this paper and the data set used in [14] showed that both situations are improbable. Therefore, in this paper the Matrix form CUSUM algorithm using averages of detected change points is used.…”
Section: Matrix Form Cusummentioning
confidence: 96%
“…Several sources simply set the all initial parameters to 1 and the hazard rate to the prior belief on the frequency of change points, but no justification has been given in the literature. A quick study [25, p. 37] using the data sets [14] revealed that setting 𝜅 and 𝛼 to one, 𝜇 to sample mean and 𝛽 being equal to the hazard rate ensures that the algorithm always finds meaningful change points. Initializing all parameters to 1 results in failing to find any change point.…”
Section: Bayesian Online Change Point Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classifiers were applied to two data sets collected from food samples. One collected from headspace, where the environmental conditions were controlled, and the other collected from an office desk without explicit attempts to control the environmental conditions (see, for example, [ 26 , 27 , 28 ] for detailed description of the data collection). The objective of the paper was to present and compare several analytical tools for improving the classification accuracy and speed for food scents also in the presence of environmental noise.…”
Section: Introductionmentioning
confidence: 99%